1832 Conn. Acts 391 - (:unkn) unknown (My University, 1832)
An Act Regulating the Mode Of Keeping Of Gunpowder, Chap. 25, § 1-2: Empowered the select-men of each and eer town within the state to remove quantities of gunpowder from the limits of their town to a place specified in the select-men's order as safe and convenient.
Keywords: GUNPOWDER - STORAGE